(untitled) (Comprehensive Journal of Science, 2025)
This scientific paper aims to examine the value dimension in critical thinking as a philosophical and educational approach that seeks to highlight the role values play in guiding intellectual action and regulating critical practice. The study is based on the assumption that critical thinking, despite its logical and analytical nature, cannot be fully achieved without a value-based framework that ethically and humanly shapes its orientation. The analytical–descriptive method was adopted in this paper to analyze the philosophical concepts that constitute the notion of values and critical thinking, while illustrating the interaction between them in light of contemporary educational and intellectual literature. The study concludes that values such as honesty, responsibility, fairness, and open-mindedness represent essential components in the formation of sound critical thinking. These values contribute to transforming criticism from a neutral intellectual practice into a responsible human act aimed at reforming thought and behavior. The findings also emphasize the need to integrate the value dimension into educational curricula and programs designed to develop thinking skills, in a manner that builds a balanced critical personality that combines rationality with ethical principles. The paper concludes that value-based critical thinking represents a comprehensive cognitive model that links rationality with ethical development, and establishes a constructive critical practice that contributes to fostering a culture of dialogue and reform within society.